2018
DOI: 10.1016/j.jid.2017.11.016
|View full text |Cite
|
Sign up to set email alerts
|

miR-596 Modulates Melanoma Growth by Regulating Cell Survival and Death

Abstract: Tumors grow because cancer cells lack the ability to balance cell survival and death signaling pathways. miR-596, a microRNA located at the 8p23.3 locus, has been shown by the TCGA-Assembler to be deleted in a significant number of melanoma samples. Here, we also validated the low levels of miR-596 in melanoma compared to tissue nevi, and Kaplan-Meier curve analysis revealed that low miR-596 expression was associated with worse overall survival. Moreover, we showed that miR-596 overexpression effectively inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
(48 reference statements)
2
12
0
Order By: Relevance
“…Consistently, we also proved the down-regulation of miR-596 in EOC cells. More importantly, our work detected From these findings, we firstly identified miR-596 as a novel tumor-inhibitor in EOC, which was similar to several previous reports regarding miR-596 function in malignancies including melanoma [14], oral cancer [25] and gastric cancer [13].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistently, we also proved the down-regulation of miR-596 in EOC cells. More importantly, our work detected From these findings, we firstly identified miR-596 as a novel tumor-inhibitor in EOC, which was similar to several previous reports regarding miR-596 function in malignancies including melanoma [14], oral cancer [25] and gastric cancer [13].…”
Section: Discussionsupporting
confidence: 88%
“…For examples, circRNA AGFG1 acts as a sponge of miR-195-5p to promote triple-negative breast cancer progression through regulating CCNE1 expression [10]; miR-760 suppresses human colorectal cancer cell growth by targeting BATF3AP-1/ cyclinD1 signaling [11]; MiR-4319 suppresses the malignancy of triple-negative breast cancer by regulating self-renewal of cancer stem cells [12]. Recently, several researches have demonstrated the tumor suppressive role of miR-596 in malignancies such as gastric cancer [13] and melanoma [14]. Besides, a former report revealed that miR-596 is expressed at a low level in EOC [15].…”
Section: Introductionmentioning
confidence: 99%
“…As a miRNA located on human chromosome 8p23.3, miR-596 acts as an antioncogene in a variety of tumors [44]. Endo et al demonstrated that miR-596 inhibited the growth of oral cancer through targeting LGALS3BP [45].…”
Section: Discussionmentioning
confidence: 99%
“…To date, vemurafenib, ipilimumab, sibutramine and other targeted drugs have been recommended for the treatment of malignant melanoma. However, malignant melanoma is not completely cured by these agents (12). Metastasis may occur during the early stages of cutaneous malignant melanoma and prognosis is often poor.…”
Section: Introductionmentioning
confidence: 99%